Effectiveness of a pharmacist-delivered smoking cessation program in the State of Qatar: a randomized controlled trial - El Hajj, Maguy Saffouh (BMC Public Health, 2017)
BACKGROUND: Cigarette smoking is one of the major preventable causes of death and diseases in Qatar. The study objective was to test the effect of a structured smoking cessation program delivered by trained pharmacists on smoking cessation rates in Qatar. METHODS: A prospective randomized controlled trial was conducted in eight ambulatory pharmacies in Qatar. Eligible participants were smokers 18 years and older who smoked one or more cigarettes daily for 7 days, were motivated to quit, able to communicate in Arabic or English, and attend the program sessions. Intervention group participants met with the pharmacists four times at 2 to 4 week intervals. Participants in the control group received unstructured brief smoking cessation counseling. The primary study outcome was self-reported continuous abstinence at 12 months. Analysis was made utilizing data from only those who responded and also using intent-to-treat principle. A multinomial logistic regression model was fitted to assess the predictors of smoking at 12 months. Analysis was conducted using IBM-SPSS® version 23 and STATA® version 12. RESULTS: A total of 314 smokers were randomized into two groups: intervention (n = 167) and control (n = 147). Smoking cessation rates were higher in the intervention group at 12 months; however this difference was not statistically significant (23.9% vs. 16.9% p = 0.257). Similar results were observed but with smaller differences in the intent to treat analysis (12.6% vs. 9.5%, p = 0.391). Nevertheless, the daily number of cigarettes smoked for those who relapsed was significantly lower (by 4.7 and 5.6 cigarettes at 3 and 6 months respectively) in the intervention group as compared to the control group (p = 0.041 and p = 0.018 respectively). At 12 months, the difference was 3.2 cigarettes in favor of the intervention group but was not statistically significant (p = 0.246). Years of smoking and daily number of cigarettes were the only predictors of smoking as opposed to quitting at 12 months (p = 0.005; p = 0.027 respectively). CONCLUSIONS: There was no statistically significant difference in the smoking cessation rate at 12 months between the groups. However, the smoking cessation program led to higher (albeit non-significant) smoking cessation rates compared with usual care. More research should be conducted to identify factors that might improve abstinence. TRIAL REGISTRATION: Clinical Trials NCT02123329. Registration date 20 April 2014